INTER-ORGANIZATIONAL COMMUNICATION COMMITMENT IN A .SUBSIDIZED MARKET OF MALAYSIAN PADDY FERTILIZER INDUSTRY - AHMAD RIZAL, AMMAR REDZA (2014)
Inter-Organization Communication (IOC) is one of the used communication disciplines to communicate between two or more organizations. It is proven vital to sustain relationship between organizations particularly between customers and suppliers. However, there is still lack of empirical research and findings in the subsidized market. Malaysian paddy farmers have been receiving fertilizers subsidy since 1971 making the environment of subsidized market stand more than 40 years long. This study presents a findings based on IOC theories of communication management between Local Farm Association (PPKs) and the supplier based on the perspectives of the PPK. It will critically discuss the elements of IOC and communication commitments based on the perspectives of PPKs. The relationship of communication willingness and communication commitment as well as mediating effect of communication behaviour and communication quality were tested in this study.